A novel eutectic phase-change material: CaCl2·6H2O + NH4Cl + KCl. (December 2018) - Dong, Ouyang; Li, Dongdong; Zeng, Dewen
Abstract: Peritectic transformation of pure CaCl2 ·6H2 O during its phase-change process limits its application as a phase change material (PCM). After modification by adding other salts, it may turn into eutectic material. In this work, the possibility of CaCl2 ·6H2 O + NH4 Cl + KCl as eutectic phase change material is studied by experiment combining computer simulation. At first, solubility isotherms of the quaternary system CaCl2 + NH4 Cl + KCl + H2 O was experimentally determined at T = 293.15 K. Secondly, phase diagrams of the quaternary system and its sub-system were simulated by a Pitzer-Simonson-Clegg model. The predicted solubility isotherms was found in good agreement with the experimental data at 293.15 K, which shows the model is reliable for this system. The solubility behavior of the system at other temperatures was predicted with the model, and an eutectic point (46.68 wt% CaCl2, 4.65 wt% NH4 Cl, 2.70 wt% KCl and 45.97 wt% H2 O) with melting temperature at 297.35 K was found existing in this system which is a promising PCM. At last, a heat storing and releasing experiment of 80 g PCM was carried out to check the possibility of the predicted material as PCM, it was found that the predicted material is an excellent PCM with latent heat of 149.6 J/g. Graphical abstract: Highlights: Solubility isotherms of the titled system were measured at 293.15 K. A PSC model was applied to simulate and predict the solubility of the system. The predicted isotherms agree with the experimental ones very well. A eutectic phase change material (PCM) has been predicted by the PSC model. The phase change behaviors of the predicted PCM were testified by experiments.